Comparison of Lipid Content in Nine Dinoflagellate Species Using Flow Cytometry - Jaeyeon Park; Eun Young Yoon; Seung Joo Moon; Jun-Ho Hyung; Hangy Lee (Microorganisms)
The lipid content of nine dinoflagellates was analyzed using flow cytometry to compare lipid levels. Additionally, the correlation between lipid content, cell size, and carbon content in dinoflagellates was evaluated using BODIPY 505/515 staining. The flow cytometry side scatter (SSC) effectively represented relative cell size, showing a linear relationship with the equivalent spherical diameter (ESD). Larger cells exhibited higher relative lipid content; however, lipid accumulation was influenced by nutritional modes and habitats, with mixorophic and benthic species displaying higher lipid content than heterotrophic species. A comparison of fluorescent dyes revealed that Nile Red overestimated lipid content, suggesting overlap with chlorophyll autofluorescence. Flow cytometry analysis with BODIPY 505/515 demonstrated a linear correlation with the sulfo-phospho-vanillin (SPV) method, enabling determination of actual lipid content using FL1 fluorescence and the slope value. As the carbon content increased, the lipid content initially increased rapidly but plateaued at higher carbon levels, indicating saturation. These findings suggest that relative fluorescence via flow cytometry provides an effective means to estimate the lipid content and carbon content as a function of cell size.